Senegal : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This Selected Issues paper and Statistical Appendix on Senegal examines the magnitude, quality, and composition of fiscal adjustment, and the sustainability of public debt in the context of a debt dynamics framework. The paper explains the rationale for fiscal adjustment and presents some characteristics of the desired tax and expenditure policies. It describes the structure and size of the public sector in Senegal, and discusses historical developments in fiscal deficits and debt accumulation. The paper also assesses the quality of fiscal adjustment in Senegal.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet